Reflection of the National Culture and Identity in the City’s Visual Identity: A Case Study of Tehran Subway Murals - A. Mahmoodi; M. Hasanpour; S. Khataie (Taḥqīqāt-i Farhangī-i Īrān, 2019)
Murals are a kind of environmental graphic designs which in addition to adding to the environment’s beauty play a significant role in shaping the visual identity of the cities and due to their structural features are widely used in subway stations. Metro environment is one of the most crowded places in today’s modern life which has a substantial impact on the society’s cultural and identity changes. The purpose of the present study was to investigate the status and role of environmental graphics as a powerful medium in fashioning and influencing the city’s visual identity as well as its role in the revival of culture, art, and national and local identity. To this aim, 70 murals of Tehran subway stations were selected and analyzed quantitatively with respect to different dimension of national identity as well as different components of its cultural dimension. Finally, the data were analyzed both qualitatively and quantitatively based on their content and structure. The data related to theoretical part of the study were gathered through library method and using the existing documents and information and the data associated with the analytical part of the study were collected through field research and employing observational tools.